Sistem Smart Farming untuk Mewujudkan Pertanian Indonesia Maju, Mandiri, dan Modern - Yudi Abdul Syawari, Muhammad; Wahyu Putri, Desmita; Hartono (LPPM Universitas Muhammadiyah Kotabumi, 2024)
Agriculture is a vital sector that serves as the backbone of society, particularly in Indonesia, which is known as an agrarian country. This sector includes sub-sectors such as food crops, horticulture, fisheries, livestock, and forestry, forming the primary source of livelihood for most of the population. However, agricultural productivity in Indonesia remains low due to the limited capacity of human resources in land management and the impact of climate change, which leads to reduced yields. Farmers often rely on manual methods to measure soil moisture, soil pH, and weather predictions, which are inefficient and prone to errors, ultimately affecting the quality and quantity of production. To address these challenges, an innovative tool has been developed to assist farmers in monitoring soil and weather conditions more accurately. This tool is equipped with sensors to measure soil moisture, soil pH, air humidity, air pressure, and wind speed. It also provides real-time weather prediction, security features through cameras and motion detection sensors, and solar panels with an inverter to generate standalone electricity. This technology allows for remote monitoring via smartphones, ensuring efficient land management, enhanced security, and sustainable energy support for farmers. By implementing this solution, it is expected that agricultural productivity in Indonesia can improve, effectively tackle climate challenges, and promote sustainability in the agrarian sector.